Building a Sustainable Job-rich Recovery. - Studies, International Institute for Labour (International Labour Office, 2011)
The European Commission and the International Labour Organization have combined efforts in reaction to the deep crisis that hit the global economy in 2008. The aim of this joint project is to examine policies that will lead not only to a quicker recovery but also to a more sustainable, environmentally friendly and equitable global economy. 'Building a Sustainable Job-rich Recovery' examines the origins of the deep financial and economic crisis of 2008 that continues to shape labour market performance across the globe.